The play is a prison: the discourse of Prison Shakespeare. Issue 2 (3rd May 2020) - Ward, Sophie; Connolly, Roy
ABSTRACT: The relationship between Shakespeare and prison was brought into sharp focus during Shakespeare's recent quad-centenary with a succession of works exploring Shakespeare's value for the prison population. In this paper, we take this spike in activity as a point of departure for examining the discourse of Prison Shakespeare. This discourse, we argue, is underpinned by several intertwining and sometimes paradoxical accounts of social being: (i) psychoanalytic accounts; (ii) postmodern accounts; (iii) humanist accounts bound up with the idea of cultural unfolding; (iv) neoliberal accounts that champion heroic individualism. In our analysis, we respond to Pensalfini's call for critical debate over the assumption that Shakespeare's plays have the power to both teach and liberate prisoners. We note how Prison Shakespeare is always in a struggle to escape the institutional power of both Shakespearean drama and the prison context itself, and the tendency of this work to provide a model of socialization into, rather than resistance against, what Bristol describes as the mode of subjectivity of the bourgeois political economy.